Ad Hoc networks to spread or not to spread?. - Andrews, Jeffrey G. (IEEE Communications magazine)
Spread spectrum communication - often called code-division multiple access - has been widely adopted over the years for many types of interference-challenged wireless communication systems including cellular and cordless telephones, wireless LANs and PANs, military applications, and global positioning systems. In this article we explore whether CDMA, in either its frequency hopping (FH) or direct sequence (DS) form, is an appropriate design approach for wireless ad hoc, or mesh, networks. One goal of this article is to help provoke a debate by explaining the main advantages and disadvantages of CDMA in the context of ad hoc networks as exposed by recent research. We argue that CDMA does not inherently improve the spectral efficiency of ad hoc networks; on the contrary, its valued interference averaging effect is not appreciable in ad hoc networks due to the irregular distribution of both the transmitters and receivers. On the positive side, both types (FH and DS) of spread spectrum allow for longer hop distances and a reversal of the usual relationship where the desired transmitter must be closer to the receiver than interfering transmitters. These two facts allow for significant advantages over narrowband systems in terms of energy efficiency and end-to-end delay.